Pengaruh Price Earnings Ratio, Debt to Equity Ratio, Dividend Payout Ratio dan Ukuran Perusahaan terhadap Nilai Perusahan - Hilda Rodhotul Ainiyah; Tumirin Tumirin (JIATAX (Journal of Islamic Accounting and Tax), 2020)
This study aims to determine the influence of price earnings ratio, debt to equity ratio, dividend payout ratio and firm size on firm value at LQ 45 company in Indonesia. This research uses quantitative methods and uses secondary data as a source of data. This research uses purposive sampling technique and has 96 company samples. This research uses multiple linear regression analysis. The results show that Price Earnings Ratio and Dividend Payout Ratio has a significant effect on firm value. Meanwhile, the variable Debt to Equity Ratio and Firm Size do not affect on firm value.